Kamala Harris and Mike Pence Personal and Social Deixis Analysis in US Vice Presidential Debate - Pramesthi, Nadia Agatha (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2024)
Personal and social deixis have been the key factors in how people can engage in a conversation or discourse. From Hamdaoui (2015), it is known that deixis is one of the linguistic techniques that politicians emphasize a lot. Any linguistic theory can study it, but pragmatics must since it informs the analyst about the context of language production, including who is speaking, to whom, when, and where (Triki, 2010). Thus, this study used personal and social deixis theory in modern linguistics to answer several research questions, such as what deixis the candidates use and what are the effects. The research aims to see how each candidate effectively draws people’s attention in a presidential debate through the analysis of social deixis. Kamala Harris chooses to be more populist by using expressions such as exclusive ‘we’ or ‘us’ and ‘you’. Meanwhile, Mike Pence focuses on presenting himself and Trump through the use of expressions such as I and inclusive ‘we’ or ‘us’. Moreover, the distant relationship with Trump’s Administration that Kamala Harris has shown to the public can be a factor in how Americans see Joe and Kamala as different figures from their predecessors.